Molecular analysis of cognitive and oxidative stress in induced-type Ibdiabetes mellitus rat treated with a-tocopherol and tocotrienol-rich fraction - Holifa Saheera Asmara
Type II diabetes mellitus (T2DM) is a global epidemic disease associated with cognitive dysfunction and oxidative stress. Treatments of a-tocopherol and tocotrienol-rich fraction (TRF) were able to improve cognitive status and reduce oxidative stress. However, their molecular mechanisms were not fully understood. Hence, the molecular alteration of mRNA with respect to specific genes expressions were studied; APP, PSEN1 and PSEN2 for cognitive, wheres MAPK9, IRS2, SOCS2, and SOCS3 for oxidative stress, and INS, PKLR and SLCA2A for diebetes. This study has been conducted on Sprague Dawley rat by inducing a T2DM were administered with of a-tocopherol and TRF respectively. The rats' cognitive status oxidative stress level, histological observation of damaged brain cells in hippocampus, and mRNA expressions wereevaluated after the supplementation period. All rats were subjected to a Morris-water maze training to determine the status of cognitive, the spatial memory, through navigation. The plasma malondealdehyde was measured to identify thi biomarker of oxidative stress. The severity of damaged brain cells was determined by hematoxylin and eosin stains. By using a microarray technique, the specified genes were analyzed for their expressions. The current study found that the blood glucose levels were significantly reduced after the supplementation period. Following the intraperitoneal glucose tolerance test, the blood glucose level was not affected by both supplements. However, during intraperitoneal insulin tolerence test, the blood glucose level were significantly reduced after both supplementation. Whilst, the induced-T2DM rats administered with TRF was more efficient in achieving the desired glucose clearance rate compared to a-tocopherol. The latencies measured in the cognitive test were improved in both supplements without a significant difference. Both supplements also reduced the oxidative stress in induced-T2DM rats. Histological findings indicated that induced-T2DM administered with a-tocopherol was able to reduce the severity of the damaged brain cells down 33.3%. Microarray analysis demonstrated that the mRNA expressions of APP, ARID5B, IKBK, INSR, MAPK9, PKLR, PSEN1, PSEN2, SLC2A2, SOCS2 and SOCS3 were significantly altered in the induced-T2DM rats, and affected by both supplements. Therefore, treatments with a-tocopherol and TRF supplements in the induced-T2DM rats, provide the prevention to cognitive impairement, increased oxidative stress, severe damaged brain cells, and harmful alteration of mRNA genes expressions.